Interactive effects of seedling number per hill and plant spacing on source-sink dynamics and yield formation in rice - Wu, Xiaoyan; Xie, Dongjie; Xu, Anjie; Yuan, Pengli; Huang, Jiada; Jiang, Ligeng (Frontiers in Plant Science, 2025)
A high-quality rice population structure serves as the foundation for achieving high yields, with plant spacing and the number of seedlings per hill playing key roles in regulating this structural development. However, the combined effects of seedling number per hill and plant spacing on yield formation and resource allocation in rice (Oryza sativa L.) are not yet fully understood. This study aimed to assess the effects of coordinated changes in seedling number per hill and plant spacing on source-sink characteristics and yield in rice, while maintaining a constant seedling density. The study evaluated the response of four rice varieties to combined variations in seedling number per hill and plant spacing, all under a baseline seedling density of 60 × 104 ha-¹, over a two-year field experiment. Linear models, mixed-effects models, ridge regression, and structural equation modeling were used to examine the effects of these factors on rice growth, biomass allocation, nitrogen and carbon accumulation, and yield. Results showed that increasing seedlings per hill and plant spacing reduced yield and above-ground biomass (AGB) but increased the harvest index (HI). Single seedlings with narrow spacing produced the highest yield (7.27 t ha-¹), AGB (16.4 t ha-¹), and the lowest HI (0.46). The combined effects of seedling number per hill and plant spacing negatively affected tiller number, number of effective panicles, leaf area index, and nutrient accumulation, while positively influencing specific leaf area and panicle biomass allocation. Organic carbon accumulation (43.52%) and biomass accumulation (31.32%) were major contributors to yield variation. Path analysis indicated that 96% of yield variance was accounted for, highlighting the importance of panicle biomass, organic carbon accumulation, and the source-sink balance between stems and panicles. In conclusion, single seedlings with narrow spacing (12.93 cm spacing with 1 seedling per hill) optimize the source-sink balance in rice, compensating for a lower harvest index by enhancing biomass accumulation, thereby increasing yield.